Implementasi Etnosains sebagai Sumber Belajar Antropologi Budaya di Prodi Industri Pariwisata - Irena Novarlia (Journal on Education, 2023)
Along with the arrival of globalization, local cultural wisdom has shifted and is often neglected. Therefore, ethnoscience is a learning resource that can be used. The aim of the research is to find out whether the Tourism Industry Study Program has implemented and described ethnoscience in learning cultural anthropology courses using qualitative research methods. The results of the research prove that the implementation of ethnoscience as a source of learning has not been properly planned but has implicitly used an ethnoscience approach through integration between the socio-cultural environment of the community and the material. Evaluation is carried out using authentic assessment. It is hoped that through the implementation of ethnoscience as a source of learning cultural anthropology it can become a bastion of cultural values ​​and local wisdom so that they are not displaced by foreign cultures and remain sustainable amidst the currents of globalization.